Perancangan E-Commerce Toko Kerupuk Udang Manda menggunakan Framework Laravel - Muhammad Aprizal; Sepriano Sepriano; Albet Triadi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
E-commerce is all activities selling goods and services carried out through electronic media. Shrimp Cracker Shop, is a business that operates in the field of selling typical souvenirs. Currently, sales of goods are still carried out manually, namely by buyers coming directly to the shop or by purchasing by telephone. This type of research uses a descriptive method with a qualitative approach. This research provides an accurate description and explanation of the conditions or symptoms faced. The materials used in this research are data obtained from the results of interviews and later the results of the interviews can find out what needs are needed to build a website. System Design Methods in Designing a The system definitely requires modeling so that the results of the system design that you want to achieve can obtain maximum results. What the author uses is Unified Modeling Langue (UML). Which consists of use case diagrams, class diagrams, and activity diagrams. In this research the author uses the Rapid Application Development system development method. The software development method in this research uses the Rapid Application Development (RAD) model system development method. After the design is carried out, the researcher draws conclusions namely the e-commerce design of the Manda Shrimp Cracker Shop was successfully created to help promotion and sales. The results of testing the Blackbox Testing software system were declared successful, and the feasibility test using a Likert scale resulted in a score of 93% (very feasible). Overall, the results were successful and in accordance with what was designed.